Strategi Pemasaran Sayuran Berbasis Digital melalui Media Online di Desa Apitaik - Sri Shanti Ariani (Lembaga Bale Literasi, 2025)
This study aims to analyze vegetable product marketing strategies through online media in the Apitaik area and to identify the differences between digital and traditional marketing patterns. Along with the rapid development of information technology, farmers in Apitaik have gradually shifted from dependence on middlemen to direct sales to consumers through digital platforms. This research employed a descriptive qualitative method, with data collected through participatory observation, in-depth interviews, and documentation involving farmers and consumers in Apitaik. The findings indicate that the use of simple social media platforms such as WhatsApp and Facebook is the most effective strategy due to their ease of operation and low cost. The main strategies implemented include the use of honest visual content, fast response services, and the application of the “Pick-and-Deliver” shipping method to maintain product freshness. Significant differences were found in the broader market reach, price transparency, and shorter distribution chain within the online system compared to the more rigid traditional system. The study concludes that the digitalization of marketing has independently increased farmers’ income and encouraged intergenerational collaboration in rural areas, although logistical challenges and limited digital literacy remain major obstacles that require attention from the government and local communities.